Evaluation of potato varieties and hybrids on the resistance against black scab under conditions of Ukraine’s Polissia - Polozhenets, V.; Nemerytska, L.; Zhuravska, I. (Quarantine and plant protection, 2021)
Goal. Assess potato varieties and hybrids for resistance against rhizoctonia disease and identify highly resistant varieties. Methods. The fundamental principle of the existing methodology for evaluating varieties is to test varieties, hybrids and species of potatoes on natural or artificial infectious backgrounds using a pure culture of the fungus Rhizoctonia solani Kuhn. The culture grown in Petri dishes was introduced when the tubers were planted in the soil. The assessment of the degree of damage to tubers and stems was carried out according to the damage to the underground organs of plants, the yield of potatoes, and then the level of variety samples was determined by resistance to the disease. Evaluation of potato varieties and hybrids for resistance against the causative agent of the disease Rhizoctonia solani Kuhn was carried out on a nine-point scale, where score 9 — no damage to stems and tubers, 7 — disease development up to 10% (high resistance); 5 — disease progression 11—25% (medium resistance); score 3 — disease progression 26—50% (low resistance). Results. Based on the test of potato varieties and hybrids for resistance against rhizoctonia, Dubravka, Vesta, Lugovska, Obriy, Serpanok, Yavir, Scarbnytsia, Tyras and hybrids P.207.407 (Zov × Polisska Rozheva), 205.17-24 (Adretta × 23-16s/73) and others; to medium-resistant (5 points) — Chervona Ruta, Povin, Vodogray, Horlytsia, Zov, Cupava, Nadiyna, Belarossa, Olvia, Svitanok Kyivskyi, Ukrainska Rozheva, Beregynia, Charunka, Okolytsia, Slutch, hybrids P.210.14-23 (Adretta × Posvit), 211.20-31 (Prolisok × Lugovska); to susceptible — 51, or 32.9% of the tested varieties. Conclusions. We have proved that mid-early ripening and early ripening cultivars as well as selection hybrids are more infected with black scab than mid-ripening, mid-late ripening and late ripening cultivars. These relatively resistant potato cultivars and hybrids are expedient to use in the selection on the resistance against black scab.